Analysis of the Influence of Tax Knowledge, Quality of Tax Services, Firmness of Tax Sanctions, and Level of Education on Taxpayer Motivation at KPP Pratama South Makassar - Vivianty D Hemeto; Darwis Lannai; Hajering Hajering (Jurnal Riset Perpajakan: Amnesty, 2024)
This research aims to test. Analysis of the Influence of Tax Knowledge, Quality of Tax Services, Firmness of Tax Sanctions, Level of Education on Taxpayer Motivation at Kpp Pratama South Makassar. The data in this research were obtained from taxpayers registered at KPP Pratama South Makassar in 2022, namely individual taxpayers who were willing to become respondents. This research uses primary data by conducting direct research in the field by giving questionnaires/statement sheets to respondents and sampling using the Siovin formula with a total of 100 taxpayers as respondents. Data analysis techniques were carried out using descriptive statistical analysis and SPSS 26.0. The results of the research show that the influence of tax knowledge has a positive and significant effect on taxpayer motivation, the quality of tax services has a positive and significant effect on taxpayer motivation, the strictness of tax sanctions has a positive and significant effect on taxpayer motivation and the level of education has a negative and insignificant effect on taxpayer motivation. Tax.